ANALISIS TERHADAP FAKTOR -FAKTOR YANG MEMENGARUHI MASYARAKAT UNTUK MENABUNG DI BANK SYARIAH - Hendi Prihanto (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2017)
A good decision in choosing a place and environment investing should pay attention to things that will be a positive value in the future. Especially in the banking industry that is currently experiencing a decline that is very meaningful for it Perceptions of trust, ease of transactions, profit sharing and security of investment is very important to note and known. This research method using quantitative method by collecting data by survey and questioner in obtaining research data, then assisted by data analysis method using a series of hypothesis testing that is linear regression analysis of t-test and coefficient of determination processed by means of statistical application tool SPSS 19.0. The result of the research shows that perception, easiness in transactions, and profit sharing have positive effect on society decision in choosing saving in syaria bank, while security guarantee have negative effect.